2016
DOI: 10.1126/sciadv.1501382
|View full text |Cite
|
Sign up to set email alerts
|

Approaching the ideal elastic strain limit in silicon nanowires

Abstract: Single-crystalline silicon nanowires can be reversibly stretched above 10% elastic strain at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
130
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 200 publications
(143 citation statements)
references
References 56 publications
11
130
1
1
Order By: Relevance
“…No hardening phenomenon is observed after it yields. The fracture stress is the same as the yield stress (14.25 GPa) which is also consistent with the experimental value (~20 GPa) [29]. However, as the KSiNWs are more spring-like, their fracture strain increases 35.58 to 0.141%, and a small hardening is observed after it yields.…”
Section: Resultssupporting
confidence: 87%
“…No hardening phenomenon is observed after it yields. The fracture stress is the same as the yield stress (14.25 GPa) which is also consistent with the experimental value (~20 GPa) [29]. However, as the KSiNWs are more spring-like, their fracture strain increases 35.58 to 0.141%, and a small hardening is observed after it yields.…”
Section: Resultssupporting
confidence: 87%
“…Comparison of the present data with the previous reports on different materials (Au, Ag, Cu, Al, Pt, and W nanowires, CNTs, BNNTs, and SiNW) in terms of elastic moduli and electrical resistivities at room temperature (different characteristic regions are marked).…”
supporting
confidence: 69%
“…MD simulations based on different interatomic potential models showed that the elastic stain of Si NWs was greater than 15% 185. Experimental measurements showed different elastic strains for Si NWs, such as 16% from the in situ TEM tensile test,217 12% from the in situ SEM tensile test,86 1.5% from the in situ SEM bending test,231 ≈5% from the nanoindentation31 and AFM bending tests,22, 31 and 4.6% and 14.7% from the respective in situ TEM tensile and bending tests 101. For SiC NWs, a maximum elastic stain of 10% was observed in an early AFM‐bending test 15.…”
Section: Mechanical Characterization Of Nwsmentioning
confidence: 99%